Analysis of a failure mechanism in parabolic troughs receivers due to bellows cap overirradiation. (April 2020) - Valenzuela, Loreto; Setien, Eneko; Zarza, Eduardo
Highlights: Solar power plants with parabolic troughs are currently available in many countries worldwide. One of the main components of the solar field is the solar receiver. Analysis of a common failure mechanism of the receiver found in commercial systems is presented. Risky operation conditions are identified and solutions to prevent the thermo-mechanical failure are suggested. Abstract: During the last years the number of broken tube receivers in parabolic-trough solar collectors was higher than expected in several commercial solar power plants and the failure events increased specially in winter. An exhaustive on field inspection of the broken glass envelopes and expansion bellows of the receivers (heat collecting elements) suggests that this unusual number of damaged receiver tubes is somewhere related with the over-irradiation of the bellows caps in some operation conditions. In this work the failure mechanism and the operation conditions that make it possible are analyzed. The analysis of this failure mechanism have allowed to identify the seasonality of the phenomenon and to design an appropriate strategy to reduce or even to prevent the failure due to the over irradiation of the bellows caps of solar receiver tubes.